Diversified crop sequences to reduce soil nitrogen mining in agroecosystems - Novelli, Leonardo Esteban (2022)
Nitrogen (N) is the primary driver of increased global food supply, but has environmental consequences from both under- and over-fertilisation. While over-fertilisation and reactive nitrogen release onto the environment is widespread in North America and Europe, under-fertilisation and soil mining prevail in South American croplands, calling for novel nitrogen-balancing strategies. The encroachment of soybean-centric, over-simplified cropping systems has eroded ecosystem services in South America. Here we compare the current soybean-centric system in Argentina with seven crop sequences in two long-term experiments started in 2008. Our aim was to identify alternative, more diverse crop sequences to maintain productivity and profitability with a close to neutral apparent N balance of the agroecosystem in two contrasting soils, i.e., a Mollisol and a Vertisol. Crop sequences combined locally adapted crops – soybean, maize and wheat for grain, field pea as cover crop – in a range from monocultures to complex sequences including all four crops. Crop sequence returned a 2.2–3.1-fold variation in productivity (from 4.7 to 10.9 Mg ha-1 in the Mollisol and from 3.4 to 9.9 Mg ha-1 in the Vertisol), 1.5-fold variation in profitability (from 0.92 to 2.14), variation in nitrogen balance from soil mining at − 35 kg N ha-1 year-1 to excess at 17 kg N ha-1 year-1, and a variation in nitrogen use efficiency at crop sequence level (NUEs) from 0.7 to 1.2 in both soil types. High soybean proportion reduced the NUEs and grain productivity of crop sequences. More complex crop sequences, i.e. including three/four crops, showed an N surplus and a similar grain yield than maize monoculture in both soils. The inclusion of maize into crop sequences with high cropping intensity increased both yield and NUEs. We identify new crop sequences that meet three conditions: high productivity and profitability, a close-to-neutral nitrogen balance, and a high nitrogen-use efficiency. These insights allow for alternatives to the current, unsustainable trajectories of simplified soybean-based systems that also avoid the path of over-fertilisation followed by cropping systems elsewhere.